Non-redox metal ions can promote Wacker-type oxidations even better than copper(ii): a new opportunity in catalyst design. Issue 40 (21st September 2015) - Qin, Shuhao; Dong, Lei; Chen, Zhuqi; Zhang, Sicheng; Yin, Guochuan
Abstract : Non-redox metal ions can accelerate Pd(ii )-catalyzed Wacker-type oxidations better than Cu(ii ), revealing a new role of Cu(ii ) in the Wacker-type mechanism. Abstract : In Wacker oxidation and inspired Pd(ii )/Cu(ii )-catalyzed C–H activations, copper(ii ) is believed to serve in re-oxidizing of Pd(0) in the catalytic cycle. Herein we report that non-redox metal ions like Sc(iii ) can promote Wacker-type oxidations even better than Cu(ii ); both Sc(iii ) and Cu(ii ) can greatly promote Pd(ii )-catalyzed olefin isomerization in which the redox properties of Cu(ii ) are not essential, indicating that the Lewis acid properties of Cu(ii ) can play a significant role in Pd(ii )-catalyzed C–H activations in addition to its redox properties. Characterization of catalysts using UV-Vis and NMR indicated that adding Sc(OTf)3 to the acetonitrile solution of Pd(OAc)2 generates a new Pd(ii )/Sc(iii ) bimetallic complex having a diacetate bridge which serves as the key active species for Wacker-type oxidation and olefin isomerization. Linkage of trivalent Sc(iii ) to the Pd(ii ) species makes it more electron-deficient, thus facilitating the coordination of olefin to the Pd(ii ) cation. Due to the improved electron transfer from olefin to the Pd(ii ) cation, it benefits the nucleophilic attack of water on the olefinic double bond, leading to efficient olefin oxidation. The presence of excess Sc(iii ) prevents the palladium(0) black formation, which has been rationalized by the formation of the Sc(iii )⋯H–Pd(ii ) intermediate. This intermediate inhibits the reductive elimination of the H–Pd(ii ) bond, and facilitates the oxygen insertion to form the HOO–Pd(ii ) intermediate, and thus avoids the formation of the inactive palladium(0) black. The Lewis acid promoted Wacker-type oxidation and olefin isomerization demonstrated here may open up a new opportunity in catalyst design for versatile C–H activations.